Process-independent workstation layout for lean automation. Issue 1 (2018) - Shigematsu, K.; Yamazaki, Y.; Kato, S.; Kojima, F.; Takata, S.
Abstract: Owing to increasing labor costs, manufacturing companies have placed importance on the implementation of inexpensive automation systems, especially in developing countries. In response to such requirements, we have proposed a lean automation system, wherein the waiting time of the material handling equipment is reduced. This is achieved by grouping the operations and allocating equipment to each operation group. With this design method, the workstations are not necessarily arranged in the order of the process sequence. In this study, we propose a method for optimizing the workstation layout to reduce the equipment transfer distance and to decrease the cost of equipment for each product. To verify the effectiveness of the proposed lean automation system, the method developed herein is applied to an electric engine control unit assembly line.